Exemplarity and Its Discontents: Hellenistic Jewish Wisdom Texts and Greco-Roman Didactic Poetry - Najman, Hindy (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2019)
This article sets up a dialogue between two bodies of ancient texts, i.e. Jewish wisdom literature and Greco-Roman didactic of the Hellenistic period, with an awareness of the scholarly and interpretive communities that have studied, taught and transformed these bodies of texts from antiquity until the present. The article does not claim direct influence or cross-pollination across intellectual, religious or social communities in the Hellenistic period. Instead, the article suggests four discrete frameworks for thinking about comparative antiquity: creation, the law, the sage and literary form. The comparative model proposed here intends to create the conditions for noticing parallels and kindred concepts. However, the article resists the temptation to repeat earlier scholarly arguments for dependency or priority of influence. Instead, the essay demonstrates remarkable alignments, suggestively similar developments, and synergies. Perhaps, the ideal first reader for this article is none other than Philo of Alexandria.